'Not All That Is White Is Lime'—White Substances from Archaeological Burial Contexts: Analyses and Interpretations. (11th January 2019) - Schotsmans, E. M. J.; Toksoy‐Köksal, F.; Brettell, R. C.; Bessou, M.; Corbineau, R.; Lingle, A. M.; Bouquin, D.; Blanchard, P.; Becker, K.; Castex, D.; Knüsel, C. J.; Wilson, A. S.; et al.
Abstract : Archaeological burial contexts may include a variety of white substances, but few analyses have been published. This study reports on the physico‐chemical characterization of such residues from seven archaeological sites. It is often assumed that white materials from burial contexts are lime. Our findings demonstrate that they can be gypsum, calcite (chalk), aragonite, brushite, degraded metal, natural (gum) resins or synthetic polymer–based products. These may be present as the result of diagenetic processes, funerary practices or modern contamination. This paper provides an analytical approach for the holistic investigation of white materials encountered in burial contexts.